STUDENTS’ PERCEPTION OF DIGITAL LITERACY BASED ACADEMIC WRITING IN INDONESIA - Andi Hudriati; Areski Wahid; Muhammad Arham; Andi Anugerah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
There are numerous studies on digital literacy, but very few connect it to the Academic Writing learning model, which makes this research urgent. It is crucial that this research be expanded upon at Universitas Muslin Indonesia in order to gather data on problems in attempts to raise the standard of academic writing instruction. In order to develop a digital Literacy Based Academic Writing learning model at Universitas Muslim Indonesia, the goal of this study is to regard students' perspectives of digital literacy on student achievement and responses. The proposed research method used an ethnographic approach to explore information about the digital literacy approach in Academic Writing learning, as ethnography is an appropriate. Since ethnography is a suitable methodology for studying academic writing, the proposed research method employed an ethnographic approach to investigate information regarding the digital literacy approach in academic writing learning. Three instructors and forty students from Universitas Muslim Indonesia were chosen by the participants. Semi structured in depth interviews, focus group discussions, and participant observation for digital literacy based Academic Writing learning model is used to gather data. Data coding, theme design, and data repetition were used to examine the data gathering. The creation of a digital literacy paradigm to know the students’ perspective at Universitas Muslim Indonesia was the outcome of this study.